Markets in historical contexts : ideas and politics in the modern world - Bevir, Mark; Trentmann, Frank (Cambridge University Press, 2004)
This book presents a much-needed corrective to the model of the 'free market' which has come to dominate public and academic life. Leading historians, theorists and social scientists offer historically-informed, interdisciplinary inquiries into the embeddedness of markets in social, cultural and political relations from the eighteenth century to the present.